Preliminary psychometric analysis of the short form of EPQ-R in a sample of college students in Lima - Dominguez Lara, Sergio Alexis (2013)
The aim of this study was to analyze the reliability of Short Form Revised Eysenck Personality Questionnaire (EPQ-R) in a sample of 309 college students (66 men, 236 women, unspecified 7) aged between 16 and 42 years (M = 20.19). The analysis of internal consistency revealed indicators of reliability and acceptable homogeneity for Extraversion (E), Neuroticism (N) and Lie (L) dimensions. The dimension Psychoticism (P) obtained a reliability below the limit considered adequate and greater difficulties in terms of the items related to the dimension. It is slope for future research to conduct a review of items of the dimensions that struggled to thus give greater meaning and be used in the Peruvian context, with the aim of providing a more reliable version of this questionnaire in this area.